-(z+6)+(2z+1)=-4(z-1)

Simple and best practice solution for -(z+6)+(2z+1)=-4(z-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(z+6)+(2z+1)=-4(z-1) equation:



-(z+6)+(2z+1)=-4(z-1)
We move all terms to the left:
-(z+6)+(2z+1)-(-4(z-1))=0
We get rid of parentheses
-z+2z-(-4(z-1))-6+1=0
We calculate terms in parentheses: -(-4(z-1)), so:
-4(z-1)
We multiply parentheses
-4z+4
Back to the equation:
-(-4z+4)
We add all the numbers together, and all the variables
z-(-4z+4)-5=0
We get rid of parentheses
z+4z-4-5=0
We add all the numbers together, and all the variables
5z-9=0
We move all terms containing z to the left, all other terms to the right
5z=9
z=9/5
z=1+4/5

See similar equations:

| x-60=720 | | 1/3(12x-24)-15=24 | | -37=9c+11-21 | | 3x^2−4 = 28 | | G(n)=n+1 | | -12=3(7-y) | | (x-4)-(x+7=8x | | 8n-2=6n-12 | | X2-10x=-21 | | 10(t+8)=120 | | 6(3z-1)-3(z+8)=8(z+1) | | 92+12=x | | C=0.10x+13.25 | | 6a=3a+24 | | 6(f-9)=-18 | | -48=12n | | 92-12=x | | 3x+20+5x+66=360 | | 5x+9=-4x-45 | | 8a=35+a | | 2(r+9)=36 | | X=5y+23 | | 6=-3{x+2} | | -6(t-2)-(t+8)=8 | | 18+6x=36x+48 | | 3x/10-3=12 | | 7x-5=3x-4+×+5 | | 9+5(x-1)=2-5(x-6) | | 12x-8x+2=12 | | -4=c/3 | | -7x-8=x-24 | | x+131=180 |

Equations solver categories